2007
DOI: 10.1590/s0034-89102007000200019
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das farmácias virtuais brasileiras

Abstract: The growing number of Internet users brought forth an increase in the search for Brazilian online pharmacy services. Aiming at evaluating the validity of information disseminated in these websites, a descriptive study was carried out in 18 virtual pharmacies concerning legal aspects, accessibility, sources of information and drug advertisings. It was found 15 pharmacies did not have authorization of the Brazilian National Health Surveillance Agency; the manager pharmaceutical offi cer's name could not be found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…That study indicated a lack of human resources and a regulatory failure of the National Health Surveillance Agency (Agência Nacional de Vigilância Sanitária -ANVISA). The study also found that the primary source of information on the sites was pharmaceutical inserts (6) . The presence of medication and health information on the Internet leads to changes in the doctor-patient relationship regarding the patient's actions of toward his or her illness: more than 70% of users claim that information contained on the Internet influences their decisions regarding prescribed treatment (7) .…”
Section: Introductionmentioning
confidence: 86%
“…That study indicated a lack of human resources and a regulatory failure of the National Health Surveillance Agency (Agência Nacional de Vigilância Sanitária -ANVISA). The study also found that the primary source of information on the sites was pharmaceutical inserts (6) . The presence of medication and health information on the Internet leads to changes in the doctor-patient relationship regarding the patient's actions of toward his or her illness: more than 70% of users claim that information contained on the Internet influences their decisions regarding prescribed treatment (7) .…”
Section: Introductionmentioning
confidence: 86%
“…Literature suggests that information plays an important role in health promotion and disease prevention 13,14,16,22,26,29,31 . Garbin et al 5 affirm that the Internet can be a great ally in the construction of health promotion projects, especially in the development of personal skills.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Medications and cosmetics are also objects of sale. This activity is carried out by online pharmacies (Quon et al 2005;Fung et al 2004;Montoya and Jano 2007;Fox et al 2005;Lanier 2004;Romero et al 2004;Lineberry and Bostwick 2004;Gondim and Falcȃo 2007;Zeman 2002;Mäkinen et al 2005;Bloom and Iannacone 1999).…”
Section: The Role Of the Internetmentioning
confidence: 99%
“…A license is granted by appointed agencies which are controlled by governmental organizations. The task of these institutions is to ensure that the sale of medications by pharmacies is in accordance with the regulations applied in the given country (Montoya and Jano 2007;Fox et al 2005;Gondim and Falcȃo 2007;Zeman 2002).…”
Section: Online Pharmacies: Legal Regulationsmentioning
confidence: 99%